Spatial Distribution, Diversity, and Activity of Microbial Phototrophs in the Baltic Sea - Xu, Peihang; Reeder, Christian Furbo; Löscher, Carolin Regina (Frontiers in Marine Science, 2022)
Microbial plankton is essential for ocean biogeochemistry. As part of the prokaryotic phototrophic microbial community, both oxygenic phototrophs (OP) and anoxygenic phototrophs (AP) are widely distributed in the ocean and may play a significant role in carbon flow and oxygen production. However, comparative studies of microbial OP and AP have received very little attention, even though their different roles might be important in various marine environments, especially in oxygen minimum zones (OMZ). We explored the spatial distribution of the microbial community in the Baltic Sea, including an OMZ region, with a particular focus on the distribution and activity of OP and AP. We used 16S rRNA amplicon sequencing in combination with a qPCR-based quantification of photosynthesis marker genes. We found that specific bacterial groups dominated surface and intermediate depths, the OMZ, and deep waters, respectively. Salinity, temperature, oxygen, and depth were significant factors explaining the microbial community composition and distribution. A high diversity of OP and AP was observed, including OP-Chlorophyta, Diatoms, Cyanobacteria and Cryptomonads, and AP-Proteobacteria and Chloroflexota. OP were more abundant at most stations compared to AP. OP showed high photosynthetic activity and more photosynthesis activity in higher temperature and upper waters, while AP photosynthesis cannot be detected in most stations. Both, cyanobacterial and eukaryotic OP preferred to live in higher temperature and upper waters, but Cyanobacteria also preferred to live in oxic water while the whole OP community showed preference to live in higher salinity area. However, AP did not show any significant hydrochemical preference but prefer to live with OP community. The Baltic Sea is exposed to multiple climate change related stressors, such as warming, decreasing salinity, and deoxygenation. This study contributes to understanding and interpretation of how microbial community, especially phototrophic groups, might shift in their distribution and activity in a changing ocean like the Baltic Sea.